2014
DOI: 10.1063/1.4861593
|View full text |Cite
|
Sign up to set email alerts
|

Multiwavelength excitation Raman scattering study of polycrystalline kesterite Cu2ZnSnS4 thin films

Abstract: This work presents a complete analysis of all Raman active modes of Cu 2 ZnSnS 4 measuring with six different excitation wavelengths from near infrared to ultraviolet. Simultaneous fitting of spectra allowed identification of 18 peaks from device grade layers with composition close to stoichiometry that are attributed to the 27 optical modes theoretically expected for this crystalline structure, including detection of 5 peaks not observed previously, but theoretically predicted. Resonance effects are assumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
153
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 267 publications
(178 citation statements)
references
References 23 publications
23
153
1
1
Order By: Relevance
“…The Raman spectrum of wurtzstannite CZGS is only dominated by a band at 362 cm -1 . On the other hand, the spectra of Figure 3 show a high similarity to the fingerprint of the kesterite CZTS [27], suggesting that these samples present the same kesterite structure. The slight red shift of the dominant bands with respect to the A modes reported by [27][28] The nature of the peak at 348-349 cm -1 , following from Lorentzian fits of the most intense A-band and particularly strong for the sample after TT3, should be discussed.…”
Section: Cztgs Thin Films Coming From Evaporation Process Flashmentioning
confidence: 95%
“…The Raman spectrum of wurtzstannite CZGS is only dominated by a band at 362 cm -1 . On the other hand, the spectra of Figure 3 show a high similarity to the fingerprint of the kesterite CZTS [27], suggesting that these samples present the same kesterite structure. The slight red shift of the dominant bands with respect to the A modes reported by [27][28] The nature of the peak at 348-349 cm -1 , following from Lorentzian fits of the most intense A-band and particularly strong for the sample after TT3, should be discussed.…”
Section: Cztgs Thin Films Coming From Evaporation Process Flashmentioning
confidence: 95%
“…The position of each Raman peak with the symmetry assignment is presented in Table I, which also contains theoretical calculations 17 and previously reported experimental data. 18 The symmetry assignment of Raman modes was done by comparing the experimentally obtained frequencies with the reported references as well as applying the rules 13 for the mode behavior to polarization measurements preformed on this sample. It can be concluded that peak positions in Table I are in good agreement with the previous work.…”
mentioning
confidence: 99%
“…Raman scattering measurements were performed with 532.0 nm excitation using a LabRam HR800-UV and 457.9 nm excitation a with T64000 Horiba-Jobin Yvon spectrometers. 13 All Raman spectra were acquired after the fabrication of the solar cell devices from which the CdS/ZnO/ZnO:Al window layer was removed using a dilute HCl solution. 14 The stoichiometric point is given by the intersection of these lines.…”
mentioning
confidence: 99%
“…3b). Kesteritic CZTS has a relatively narrow and dominant Raman shift at 338 cm -1 from the A 1 mode, with further peaks at 288 (A mode), 358 (B mode) and 372 cm -1 (B mode) [61,62]. This is seen in the films heated at higher temperatures ([400°C).…”
Section: Resultsmentioning
confidence: 55%